Urban public knowledge towards Sarcopenia: health education needs assessment - Noor Hasliza, Che Seman *; Chin, Che Chong (HH Publishers, 2023)
Introduction: Sarcopenia is increasingly recognized as a health problem among older persons and is one of the major determinant factors in frailty. Studies revealed sarcopenia is prevalent in Malaysia and it have detrimental impact on the quality of life of older people. Sarcopenia can be prevented with adequate knowledge and practices on controlling the risk factors. This study aimed to assess the urban public’s knowledge on sarcopenia. Methods: A cross-sectional online survey was conducted among urban population in one of the states in Malaysia. Data was collected from October to December 2020. Results: A total of Two hundred and two publics participated in the study. The present study revealed that only 14 (6.9%) of the participants were found to possess good knowledge about sarcopenia with mean age was 49.0 years (SD = ±12.65. Analysis of variance indicated statistically significant differences at the < 0.05 significance level for age group, gender, educational level and smoking habit. Conclusion: The findings highlight the lack of sarcopenia knowledge among the urban public. This study indicated urban public are not well-informed about sarcopenia and lack of health promotion strategies to address this alarming public health problem. The study findings have identified the health education needs and will contribute to the development and implementation of an evidence-based health promotion programme serve as data for health promotion programme towards sarcopenia and its prevention.